The technology of receiving finely dispersed powders of magnetic materials in the screw drum - Vernigorov Yuriy; Frolova Natalia (MATEC Web of Conferences, 2017)
It is experimentally shown the possibility of obtaining a finely dispersed powder using mills of non-impact type on the basis of the screw drum. The dependence of grinding the powder to the weight of the load is proved.